Mucormycosis infection in severe COVID‐19 patient with multiple underlying health conditions - Zahra Heydarifard (Wiley, 2021)
Abstract Patients with underlying health conditions are vulnerable to invasive fungal infection following COVID‐19. It seems that uncontrolled diabetes mellitus makes patients susceptible to both severe COVID‐19 and mucormycosis.